PELATIHAN PASSING KE DINDING EMPAT REPETISI LIMA SET SELAMA ENAM MINGGU LEBIH BAIK DARIPADA PELATIHAN PASSING BERPASANGAN EMPAT REPETISI LIMA SET SELAMA ENAM MINGGU DALAM MENINGKATKAN KETEPATAN TEMBAKAN BOLA PADA SISWA PUTRA SDN 3 GERIMAX INDAH LOMBOK BARAT 2015 - Misi, Martin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Football is part of the game that aims to try to put the ball into the opponent’s goal. The fact that many players do not have the ability to make shots towards the goal. So it is necessary to create an exercise program that aims to improve the accuracy of the shot towards the goal. the training model provided is passing to wall training and paired passing training. The study was conducted with pre and post test group design at SDN 3 Gerimax Indah. Descriptive analysis shows the anthropometry of the subject of research with the same characteristics. The result of the t-paired improvement test shows the initial score of l-12.58 and the group- ah score of 28.83 with p = 0.000.dan the initial score of the group-2 11.25 and the ahir score of group-2 20.50 p = 0.000, Different test results with t-independent test showed initial scores of group-l 12.58 and initial score of group-2 11.25 with p = 0,083 and score ahir group-l 28,83 and final score of group-2 20, 50 with p value = 0.000. From result of t-paired and t-independent test obtained p <0,05. Show that this training is different meaningful. This is due to the training passing to the wall more focus and more concentration on the ball. The conclusion of passing to wall training is better than paired passing training in improving the accuracy of shooting at SD Negeri 3 Gerimax Indah football game. It is therefore advisable to trainers and sports teachers who train soccer branches to apply passing training to the walls in training.